Mini Review Efek Hipokolesterolemik Germinated Brown Rice terhadap Penurunan Risiko Penyakit Kardiovaskular - Luh Desi Puspareni (Medika Respati : Jurnal Ilmiah Kesehatan, 2020)
Background: Diet is an important factor in cardiovascular disease. Germinated brown rice (GBR) can be used as a dietary option in the management of cardiovascular disease. Invitro data and animal experiments show that GBR has a hypocholesterolemic effect that can reduce the risk of cardiovascular disease. Objective:. to explore the hypocolesterolemic effects of GBR as an effort to manage nutrition to reduce the risk of cardiovascular disease and the potential for GBR as part of the management of nutrition in cardiovascular disease. Methods: This study uses the literature review method. Artukel selection uses an electronic database in the form of Scopus, ScienceDirect, Open Access Library (OALIB), Google Scholar, and Pubmed. Publication searches are conducted with restrictions between 2013 and 2015. Result : Invitro data and animal experiments show that GBR has a hypocholesterolemic effect that can reduce the risk of cardiovascular disease. GBR bioactive compounds such as am-aminobutyric acid (GABA), γ-oryzanol, dietary fiber, phenolics, vitamins, and acylated steryl β-glucoside can be used as lipid profiles, increased gene related to consumption, and increased lipolysis. Conclusion: consumption of GBR can reduce the risk of cardiovascular disease.